PENGARUH KEPEMIMPINAN KEPALA MADRASAH DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU MADRASAH ALIYAH KABUPATEN GROBOGAN - Wagito Wagito; Nurkolis Nurkolis; Yovitha yuliejantiningsih (Magister Manajemen Pendidikan, Universitas PGRI Semarang, 2016)
Teacher performance is the ability to carry out duties or work in accordance with the attitude, knowledge and skills as well as motivation. Preliminary survey results show that the performance of teachers in performing the tasks teacher at Madrasah Aliyah Madrasah working group 02 Grobogan which shows that the majority of teachers in the teaching job is not done in structure. Such conditions may ultimately have an impact on graduation rates of learners. The objective of this research was to examine (1) the influence of headmaster leadership on teacher performance Madrasah Aliyah (2) the influence of organizational culture on teacher performance Madrasah Aliyah and (3) the influence of headmaster leadership and organizational culture on teacher performance Madrasah Aliyah Grobogan.The approach and type of research is quantitative. The population of this study were all teachers Madrasah Aliyah Working Group Madrasah 02 Grobogan totaling 831 with a sample of 125 teachers. Data were collected by questionnaire and analyzed using multiple regression equation with SPSS. 21.The results of this study using empirical data show that (1) leadership headmaster proved influential positive significantly to the performance of Master Madrasah Aliyah Working Group 02 Grobogan, (2) organizational culture proven significant positive effect on the performance of teachers Madrasah Aliyah Working Group 02 Grobogan, (3) headmaster leadership and organizational culture together proven significant positive effect on the performance of teachers Madrasah Aliyah Working Group 02 Grobogan.Referring to the results of this study suggested that some of the things is that in order to improve the performance of teachers in Madrasah Aliyah Working Group Madrasah 02 Grobogan need to improve leadership and organizational culture.